Stability and rheological behaviour of functional essential oils in glycolipid cream emulsion / Saw Mei Mei - Saw, Mei Mei (2013)

(untitled)
Essential oils carries distinctively unique aroma from parts of a plant where they are extracted. Essential oils have widely been known for its aromatherapy and therapeutic effect on human. High concentration of essential oil comprises of thyme, lavender, tea tree and citronella oil have been induced in emulsions system using olive oil as carrier oil stabilized by glycolipid surfactants of sucrose stearate, surcrose palmitate and sucrose myristate respectively. Co-surfactants, TritonTM X-100 and TritonTM X-45 was utilised to create high interactions and compatibility associated with short chain terpenes, terpenoids and phenolic compound presents in essential oils inverting emulsion droplet forming o/w emulsion system. Essential oil emulsions were subjected to a series of physical properties evaluation specifically accelerated ageing test conducted at 45.0±0.1 °C, zeta potential, mean droplet size measurement and polarising microscope observation. Rheological evaluations by mean of oscillatory and viscometric studies were carried out at constant temperature of 30.0±0.1 °C over the period of 30 days. Viscometric flow curve shows shear thinning behaviour for all essential oil emulsions exhibiting reduction of yield stress directly proportionate with reduction of lipid chain length. Mean droplet size and PDI govern the variation of viscosity of thyme and lavender oil where large droplet forming uniform distribution yield high viscosity emulsion possessing strong structural integrity with high critical strains and G’ magnitude. Frequency dependent shear oscillation display dominancy of G’ over G” throughout the measured frequency (ω) domain implicates emulsions system exhibiting solid like behaviour. Thyme and lavender essential oil emulsions possessing higher G’ and viscosity was concluded to be more stable than tea tree oil and citronella emulsions. All the emulsion tested possessed a long shelf life sustaining high emulsion fractions over 30 days of storage.